"A Prison Ship Lies Waiting in The Bay": Penal Colonialism in the South Pacific - Boast, RP (Victoria University of Wellington Law Review, 2023)
This article is offered as a contribution to this festschrift in honour of Professor Tony Smith, my colleague at Victoria University of Wellington. The main purpose of the article is to provide a Pacific orientation to the history of English criminal law and criminal and penal administration, as part of a collection of articles written as a tribute to Professor Smith’s expertise and prominence in criminal law. The article draws on the historiography of English criminal law, a historiography with which Professor Smith is very familiar (and, indeed, knows some of its contributors personally). The article links this historiography to the wider historiography of the Pacific. Although the main focus is on Great Britain and the British system of convict transportation in the 18th and 19th centuries, the article also considers its French equivalent. France, too, shipped convicts to the Pacific, and just as the architectural legacy of the transportation era is obvious in Australia and Norfolk Island, it is also obvious in New Caledonia. The main approach has been to focus on "penal colonialism" as a specific variety of colonialism in its own right, and as an important dimension of British and French colonialism in the Pacific region during the colonial era. While New Zealand was not a penal colony as such, New Zealand had some connections of its own with British penal colonialism in the southwestern Pacific: New Zealand sent some convicts to the Australian penal colonies in New South Wales in Van Diemen’s Land and also possessed a small-scale internal transportation of its own.